The Impact of Static and Dynamic Working Capital on Growth of Manufacturing Firms in Pakistan - Bilal Ahmed, Chishty (Universiti Malaysia Sarawak (UNIMAS), 2021)
The main objective of this research is to determine the impact of working capital management (WCM) on the growth of manufacturing firms in Pakistan. This study mainly targets four separate analyses for measuring the impact of static WCM and dynamic WCM on firms' internal and sustainable growth of the manufacturing firms in Pakistan. A total of 174 companies were selected as study sample over a period of 2007 to 2016. The study employed Static panel regression over a balanced panel data namely, pooled ordinary least square (POLS), Random Effect Model (REM), Fixed Effect Model (FEM) using Hausman test specification. Additionally, a series of diagnostic tests was also performed namely, multicollinearity, heteroscedasticity, and serial correlation test. The findings of the study revealed that static WCM measures (Current Ratio) have a significant negative impact on firms' internal growth. Dynamic WCM measures namely, days sales outstanding DSO and inventory turnover ITO has a significant negative impact on firms' internal growth rate, leverage and current assets investments have also impacted significantly on firms' internal growth. For sustainable growth models, the findings of this study revealed that static WCM does not have any significant impact on the firm's sustainable growth. Moreover, inventory turnover (ITO), and payable deferral period (PDP) which are dynamic WCM measures, show a significant impact on firms' sustainable growth rate. The overall results confirmed that dynamic WCM measures ITO, and PDP predicted firms' internal and sustainable growth rate significantly. This suggests that the Firms will have more internal growth with low liquidity by maintaining the investment in ITO and DSO. Similarly, findings suggest that high investment in ITO and less use of supplier's credit (PDP) may lead to positive results in the sustainable growth of firms. The study further confirmed that size, leverage, dividend payout ratio, and current assets investment policy are critical tools that minimize the risk of achieving a high level of the internal and sustainable growth rate of firms in Pakistan. Based on study findings, it is suggested that business leaders may incorporate optimum use of working capital management practices into overall corporate business policy, thereby aligning working capital requirements with the changing business requirements that support firms' growth internally and sustainably. Moreover, results in the research would be utilized in the efficient identification and exploration of working capital management practices among listed manufacturing sectors of Pakistan in the future.